Propuesta de estudio ambiental para desarrollar la actividad de pequeña minería no metálica caliza, en el distrito de Jepelacio, provincia de Moyobamba - Bartra Leveaú, René Gabriel (2015)
The activity of non-metallic mining in San Martin region 1s mcreasing. The informality of this activity was noted in the environmental impacts that they generate within the resource flora, soil, water, air, wildlife and beautiful landscapes, in this context from April, 2012 the Cabinet's Presidency by means of the D.S. N°1105, has implemented a formalization come from mining that seeks to promote the formalization of the activity through the compliance of environmental tools and techniques that minimize the potential environmental impacts. Through this research work was able to determine the type of environmental study you must perform, environmental baseline, methodology of environmental assessment, environmental management, monitoring, and closure of the quarry of non-metallic mining extraction of limestone in the mining concession The Lord Jhire 1, located in the jurisdiction of Jepelacio district; to do this were planned field work that consisted of the evaluation in the field of the recognition of the environmental components such as soil, water, air, vegetation, and socioeconomic that are being impacted and so set the potential negative impacts and positive activity that are creating and will generate organized and valued through Leopold array, for later establish the mechanisms of mitigation, control and prevention through the environmental management plan, monitoring and contingency. As part of the results is established that the mining concession The Lord Jhire 1, located in the jurisdiction of Jepelacio district is located within the category of artisanal mining by presenting a concessioned surface of 100ha., and a daily production of 25 MT of non-metallic mineral Limestone removed, to which he belongs to an environmental study of Category 1 - Environmental lmpact Statement. The removal stage - operation received the highest rating average negative in magnitude of -4.19 and 4.91 in importance, a process that has been impacting environmental components such as soil, geomorphology, geology, natural capacity, interna! and externa! geodynamics, vegetative cover, fauna and socioeconomic status; these components are prioritized in the mitigation alternatives, prevention, and control of the potential environmental impacts of the proposed environmental management, as well as the respective follow through of the monitoring and closure of the quarry, giving priority to the quality of the soil, air quality, quality of the biological environment and socio-economic. Key words: non-metallic mining; mitigation alternatives.